Highly porous Ti–Ni anodes for electrochemical oxidations. Issue 8 (8th June 2020) - Guenani, Nihal; Barawi, Mariam; Villar-García, Ignacio J.; Bisquert, Juan; de la Peña O'Shea, Víctor A.; Guerrero, Antonio
Abstract : Powder metallurgy enables the fabrication of scalable and efficient electrodes for oxidation reactions. Abstract : This work describes a general method to obtain highly porous electrodes and their use as dimensionally stable anodes for the O2 evolution reaction (OER). By using a powder metallurgy based process, where metallic titanium and nickel powders are pressed and thermally treated to form "brown compacts", we obtain electrodes that benefit from a 1000-fold increase in the electrochemical surface area (ECSA). In addition, active catalytic species for water oxidation ( i.e. NiOOH) are generated during the processing converting these electrodes as ideal candidates for evaluation in oxidation reactions. Excellent OER performance is obtained with overpotentials below 270 mV at 10 mA cm −2, exceeding those of commercially available alternatives. The current work paves the way for a generic method that will be extended to other electrochemical reactions.